Comparative Education in Zoology Teaching: a historical-curricular analysis - Hugo José Coelho Corrêa de Azevedo; Rosane Moreira Silva de Meirelles (Universidade Cruzeiro do Sul, Ensino de Ciências e Matemática, 2022)
This paper presents a historical analysis of Zoology curricula in Brazil, based on comparative education. Data were collected in six documents that portray the historical context from the curricular structure of Colégio Imperial de Pedro II to the National Common Curricular Base. The following criteria for comparison and analysis were used: zoological curriculum discourse, scientific content, method used and historical context. The results showed that the teaching of Zoology has historically passed through 4 curricular phases, namely: 19th century from the 19th century and the Brazilian Empire, Positivist from the Cold War and technological dispute, Technicists from the military dictatorship and the progressive discourse and Skills and Competencies that arise at the time of discussion of post-critical theories of curriculum in Brazil. It is concluded that the Teaching of Zoology suffered political and social determinants that influenced its conceptual perspectives and zoological curricular discourse during the period used.